La trame de l’enquête articulée avec le cours d’action pour étudier l’activité collective en contexte éducatif - William Larosa; Serge Leblanc (Activités)
In a context where multiple partnerships are developing in the field of education (Marx and Reverdy, 2020), we analyzed the activity of a collective of actors with different statuses (primary school teacher, volunteer and swimming instructor) in the context of teaching swimming skills. By following the course-of-action research program (Theureau, 2004, 2006, 2015) and linking it to the theory of inquiry (Dewey, 1938), we were able to determine how the experience of these actors was transformed over the course of collective activity. In this way, we were able to show that all the actors were continually moving beyond institutional prescriptions. This constancy, supported by a range of processes, led to an enrichment of knowledge within the collective. These elements open up new avenues on two levels. On the one hand, given a large corpus of data, they allow us to consider the theoretical and methodological contributions of this research as an effective means of gaining dynamic access to the consensual activity of actors over a long period of time. From a technological perspective, they also help to clarify the mechanisms of experiential reciprocity at play within a partnership.